Contextual Effect of the Integrated Health Post on DPT3 Immunization Uptake among Infants in Wonogiri, Central Java - Inayati, Rizqi; Rahardjo, Setyo Sri; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: DPT3 immunization coverage is considered as one indicator of the success of immunization programs in various countries. Indonesia is one of the countries that adopted Expand Program in Immunization (EPI) in 1977 which later introduced DPT as part of routine basic immunization services for infants, although there are still infants who do not get complete DPT immunization at this time. The purpose of this study was to analyze contextual effect of the integrated health post on DPT3 immunization uptake among infants in Wonogiri, Central Java.Subjects and Method: This was an analytical observational study with a cross sectional design. It was conducted in Wonogiri community health center II, East Java, from October to December 2018. A sample of 200 infants was selected from 25 integrated health posts with simple random sampling. The dependent variable was the use of DPT3 immunization. The independent variables were maternal education, family income, religion and beliefs, family support, information exposure, attitude, subjective norm, perceived behavior control, and intention. The data were collected by questionnaire and analyzed by a multilevel logistic regression.Results: The use of DPT3 immunization was influenced by maternal education (b = 2.01; 95% CI= 0.26 to 3.76; p= 0.025), family income (b= 2.56; 95% CI= 0.45 to 4.67; p= 0.017), religion and beliefs (b= 4.37; 95% CI= 1.78 to 6.96; p= 0.001), family support (b= 1.92; 95% CI= - 0.07 to 3.90; p= 0.058), exposure to information (b= 1.82; 95% CI= 0.11 to 3.54; p= 0.037), attitude (b= 1.59; 95% CI= - 0.29 to 3.47; p= 0.097), subjective norm (b= 1.66; 95% CI= - 0.17 to 3.49; p= 0.074), perceived behavior control (b= 2.50; 95 % CI= 0.57 to 4.43; p= 0.011), and intention (b= 2.93; 95% CI= 0.68 to 5.19; p= 0.011). Integrated health post had strong contextual effect on the use of DPT3 immunization with ICC= 53%.Conclusion: The use of DPT3 immunization is influenced by maternal education, family income, religion and beliefs, family support, exposure to information, attitude, subjective norm, perceived behavior control, and intention. Integrated health post has strong contextual effect on the use of DPT3 immunization.Keywords: DPT3 immunization, factors, Theory of Planned Behavior, posyandu, information exposureCorrespondence: Rizqi Inayati. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta, Indonesia. Email: inayati.rizqi12@gmail.com. Mobile: +6289681682143Journal of Maternal and Child Health (2019), 4(4): 267-278https://doi.org/10.26911/thejmch.2019.04.04.06